Program Pengelolaan Kebersihan Lingkungan di Pesantren - Elizabeth, Misbah Zulfa (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
Hygiene management is an issue that is very important for the sustainability of a healthy environment. However, people in general seem difficult to implement a clean and healthy life. The presence of plastic in conjunction with the development of manufacturing has resulted into a big problem for the environment. On the other hand,Â Islam strongly encourages cleanliness and environmental management. Based on the above considerations by taking the focus of activities in Islamic boarding house, and to use â€œdialog wargaâ€approachÂ with the ABCD method,Â this program aims to change the behavior of students to be aware of the importance of hygiene, garbage sorting and understand the principle of using the principles of reuse, reduce and recycle. After the end of the program found that the process of habituation behavior of cleanliness must be preceded by changes in the knowledge system.